Índice de iluminación aplicando normativa iberoamericana para determinar distancia de visibilidad en accesos a túneles del corredor vial e-30” - Inca Morales, Pedro Iván (2023)
The main objective of this work is to evaluate the lighting design in the existing tunnels on the E-30 road, applying the current regulations in Spain, Colombia, and Peru. During the investigation, the need to evaluate the tunnel entrances and stopping sight distance was detected due to the apparent lack of lighting in the entrances, which produces a perception of a black hole from the outside. Additionally, it was identified that the implementation of safety and evacuation signage could improve the efficiency of tunnel entrances, ensuring better orientation and evacuation in case of emergency. After conducting technical visits and collecting the necessary data for calculations, it was determined that the lighting levels in the tunnel entrances exceed the established average values, indicating that the lack of light is not the cause of the black hole sensation when approaching the tunnels. Although the stopping sight distance was considered acceptable in terms of safety, the implementation of signage would improve the functionality aspect.